Well-defined palladium(II) complexes for ligand enabled C(sp3)-alkynylation - Landge, Vinod Gokulkrishna; Sahoo, Manoj Kumar; Midya, Siba Prasad; Jaiswal, Garima; Balaraman, Ekambaram (Dalton Transactions, 2015)
The first example of ligand-enabled C(sp3)-alkynylation of 8-methylquinoline is reported. The reaction is catalysed by well-defined Pd(II) complexes. The present C(sp3)-alkynylation has a broad substrate scope as well as functional group tolerance and proceeds efficiently under mild conditions.

Cobalt-catalyzed bis-alkynylation of amides via double C–H bond activation - Landge, Vinod Gokulkrishna; Jaiswal, Garima; Balaraman, Ekambaram (Organic Letters, 2016)
The first example of cobalt-catalyzed selective bis-alkynylation of amides via double C–H bond activation with the directing assistance of a removable bidentate auxiliary is reported. The developed alkynylation strategy is simple, efficient, and tolerant of various functional groups including ether, amine, halides, and heterocyclic motifs. The reaction can be scaled up under mild conditions.

Earth abundant iron-rich N-doped graphene based spacer and cavity materials for surface plasmon-coupled emission enhancements - Srinivasan, Venkatesh; Vernekar, Dnyanesh; Jaiswal, Garima; Jagadeesan, Dinesh; Ramamurthy, Sai Sathish (ACS Applied Materials & Interfaces, 2016)
We demonstrate for the first time the use of Fe based nanoparticles on N-doped graphene as spacer and cavity materials and study their plasmonic effect on the spontaneous emission of a radiating dipole. Fe-C-MF was produced by pyrolizing FeOOH and melamine formaldehyde precursor on graphene, while Fe-C-PH was produced by pyrolizing the Fe-phenanthroline complex on graphene. The use of the Fe-C-MF composite consisting of Fe-rich crystalline phases supported on N-doped graphene presented a spacer material with 116-fold fluorescence enhancements. On the other hand, the Fe-C-PH/Ag based cavity resulted in an 82-fold enhancement in Surface Plasmon-Coupled Emission (SPCE), with high directionality and polarization of Rhodamine 6G (Rh6G) emission owing to Casimir and Purcell effects. The use of a mobile phone as a cost-effective fluorescence detection device in the present work opens up a flexible perspective for the study of different nanomaterials as tunable substrates in cavity mode and spacer applications.
Keywords: Casimir effect; fluorescence enhancements; iron carbides; N-doped graphene; Purcell factor; surface plasmon-coupled emission

Nickel-catalyzed direct alkynylation of C(sp2)-H bonds of amides: an “inverse sonogashira strategy” to ortho-alkynylbenzoic acids. just accepted - Landge, Vinod Gokulkrishna; Shewale, Chinmay H.; Jaiswal, Garima; Sahoo, Manoj Kumar; Midya, Siba Prasad; Balaraman, Ekambaram (Catalysis Science & Technology, 2016)
Nickel-catalyzed direct alkynylation of C(sp2)–H bonds of amides using commercially available, inexpensive 8-aminoquinoline as a removable bidentate directing group is described. The present ortho-alkynylation has a broad substrate scope, functional group tolerance and high regiocontrol, and can be scaled up. The efficiency and selectivity of this strategy provide sustainable routes to a diverse array of ortho-alkynylbenzoic acids under Ni(II)-catalyzed conditions.

Sustainable Iron-catalyzed direct imine formation by acceptorless dehydrogenative coupling of alcohols with amines - Jaiswal, Garima; Landge, Vinod Gokulkrishna; Jagadeesan, Dinesh; Balaraman, Ekambaram (Green Chemistry, 2016)
The Acceptorless Dehydrogenative Coupling (ADC) of alcohols with amines is reported using a heterogeneous Fe-catalyst. The reaction operates under mild conditions with the liberation of dihydrogen and water as the byproducts. The developed ADC strategy is simple, efficient, exhibits wide functional group tolerance and can be scaled up. The present catalytic approach possesses a dual role; acting as a catalyst as well as being magnetically separable. The sustainable reuse of a heterogeneous iron catalyst is also shown.

Iron-based nanocatalyst for the acceptorless dehydrogenation reactions - Jaiswal, Garima; Landge, Vinod G.; Jagadeesan, Dinesh; Balaraman, Ekambaram (Nature Communications, 2017)
Development of sustainable catalytic systems for fundamentally important synthetic transformations and energy storage applications is an intellectually stimulating challenge. Catalytic dehydrogenation of feedstock chemicals, such as alcohols and amines to value-added products with the concomitant generation of dihydrogen is of much interest in the context of hydrogen economy and is an effective alternative to the classical oxidation reactions. Despite a number of homogeneous catalysts being identified for the acceptorless dehydrogenation, the use of high price and limited availability of precious metals and poor recovery of the catalyst have spurred interest in catalysis with more earth-abundant alternatives, especially iron. However, no report has described a reusable iron-based heterogeneous catalyst for oxidant-free and acceptorless dehydrogenation reactions. Here we replace expensive noble metal catalysts with an inexpensive, benign, and sustainable nanoscale iron catalyst for the efficient acceptorless dehydrogenation of N-heterocycles and alcohols with liberation of hydrogen gas.

Iron-catalyzed dehydrogenation reactions and their applications in sustainable energy and catalysis - Balaraman, Ekambaram; Nandakumar, Avanashiappan; Jaiswal, Garima; Sahoo, Manoj K. (Catalysis Science & Technology, 2017)
Inspired by nature, chemists have designed new catalysts in the pursuit of selective bond activation and chemical transformations. Emergent biological systems often use earth-abundant first-row transition elements as catalytically active sites to facilitate specific and highly selective chemical processes. The design of a new catalytic system based on abundant and inexpensive catalysts, particularly the iron-based catalysts, for fundamentally significant synthetic transformations under environmentally benign conditions is an important paradigm in chemical synthesis. In recent times, iron-based catalytic systems have shown unprecedented reactivity in the acceptorless dehydrogenation reactions of feedstock chemicals, with the liberation of molecular hydrogen as the by-product, and have enabled greener chemical synthetic methods and alternative energy storage systems. Indeed, it has been demonstrated that the proper design of iron catalysts by judiciously choosing ligands, can aid in the development of new sustainable energy storage systems and catalysis. This tutorial review focuses on the recent development of iron-based dehydrogenation reactions of fundamentally important feedstock, as a route to sustainable chemical synthesis and energy storage applications. The emerging area of the iron-based dehydrogenation strategy provides an opportunity to make industrially applicable, cost-effective and environmentally benign catalytic systems.

Organo-photoredox catalyzed oxidative dehydrogenation of N-heterocycles - Sahoo, Manoj K.; Jaiswal, Garima; Rana, Jagannath; Balaraman, Ekambaram (Chemistry-A European Journal, 2017)
We report here for the first time the catalytic oxidative dehydrogenation of N-heterocycles by a visible-light organo-photoredox catalyst with low catalyst loading (0.1-1mol%). The reaction proceeds efficiently under base- and additive-free conditions with ambient air at room temperature. The utility of this benign approach is demonstrated by the synthesis of various pharmaceutically relevant N-heteroarenes such as quinoline, quinoxaline, quinazoline, acridine, and indole.

Photocatalysis enabling acceptorless dehydrogenation of diaryl hydrazines at room temperature - Sahoo, Manoj K.; Saravanakumar, Krishnasamy; Jaiswal, Garima; Balaraman, Ekambaram (ACS Catalysis, 2018)
Aromatic azo compounds are privileged structural motifs, and they exhibit a myriad of pharmaceutical as well as industrial applications. Here, we report a catalytic acceptorless dehydrogenation of diarylhydrazine derivatives to access a wide variety of aryl-azo compounds with the removal of molecular hydrogen as the sole byproduct. This distinctive reactivity has been achieved under dual catalytic conditions by merging the visible-light active [Ru(bpy)(3)](2+) as the photoredox catalyst and Co(dmgH)(2)(py)Cl as the proton-reduction catalyst. The reaction proceeds smoothly under very mild and benign conditions and operates at ambient temperature. This dual catalytic approach is highly compatible with many different functional groups and has a broad substrate scope. We have also demonstrated the reversible hydrogen storage and release phenomenon on hydrazobenzene/azobenzene couple to show the utility of these compounds as hydrogen storage materials. Further diversification of azobenzene was shown by a transition metal-catalyzed azo-group-directed ortho-C-H bond functionalization.
Keywords: acceptorless dehydrogenation; Azo benzene; dual catalysis; Hydrogen; photoredox catalysis

Reusable cobalt catalyst for reversible acceptorless dehydrogenation and hydrogenation of N-Heterocycles - Jaiswal, Garima; Subaramanian, Murugan; Sahoo, Manoj K.; Balaraman, Ekambaram (ChemCatChem, 2019)
<span style="color: rgb(42, 45, 53); font-family: "Source Sans Pro", Arial, Helvetica, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(248, 248, 248);">The development of robust catalytic systems based on basemetals for reversible acceptorless dehydrogenation (ADH) and hydrogenation of feedstock chemicals is very important in the context of ` hydrogen storage'. Herein, we report a highly efficient reusable cobalt-based heterogeneous catalyst for reversible dehydrogenation and hydrogenation of N-heterocycles. Both the ADH and the hydrogenation processes operate under mild, benign conditions.